Driving Mobile Accounts Sales: Strategic Imperative for Telenor Pakistan. Issue 2 (September 2019) - Awan, Muhammad Luqman; Awan, Muhammad Usman; Naseer, Omer; Khan, Usman Mumtaz
In October 2013, Mahboob Ali Shah Manager Financial Services Planning Telenor Pakistan (TP) needed to make decisions on the future of Mobile Accounts Sales officers (MASOs). TP had two businesses, i.e., GSM (96 per cent revenue contribution in TP 2012 sales) and financial services offering (4 per cent revenue contribution in TP 2012 sales) under the brand name of EasyPaisa. TP launched EasyPaisa in 2009 with a view to reach out to the unbanked segment (60 million people). By 2012, EasyPaisa had a brand awareness of 80 per cent with the largest footprint of 36, 000 EasyPaisa shops. Mobile accounts (MAs) were introduced in 2010 which could be operated only by Telenor sim and; hence, offered a great opportunity for TP to attract and retain customers for continual usage of its complete offerings. TP developed an elaborate go to market strategy (direct as well as indirect) to reach its customers effectively. Territory Sales Supervisors (TSS) has been the focal contact point between TP and their franchises since the launch of GSM services in 2005; however, as TP increased their offerings in the realm of financial services and offered diverse services such as MAs it became difficult for TSS to focus on MA and other financial services products whereas ironically MA contributed only (5 per cent) in KPI of TSS. At the same time, selling of MAs required different selling process as opposed to selling GSM services to franchisees and subsequently to retailers. Due to this change in the selling process, highly successful TSS had not been able to achieve sales targets for MA. In order to achieve corporate objectives for MA sales, Mahboob needed to make a choice from among different possible options for MASO's expansion to achieve this year's target of 350, 000 MA, out of which until now he could achieve only 224, 000.